2017
DOI: 10.18632/oncotarget.16182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gadolinium-enhanced MRI and 18FDG PET/PET-CT for the diagnosis of brain metastases in lung cancer patients: A meta-analysis of 5 prospective studies

Abstract: ObjectiveWe undertook this meta-analysis to compare the significance of Gadolinium-enhanced MRI and 18FDG PET/PET-CT for diagnosing brain metastases of lung cancer patients.ResultsFive articles comprising 941 patients were included for analysis. The sensitivities with 95% confidence interval for PET/PET-CT and MRI were 0.21 (0.13 − 0.32) and 0.77 (95% CI = 0.60 − 0.89), specificities were 1.00 (0.99 − 1.00) and 0.99 (0.97 − 1.00), and the areas under curve were 0.98 (0.96 − 0.89) and 0.97 (0.96 − 0.98).Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Twenty-four meta-analyses on the use of PET or PET/CT with different tracers in brain tumors, published from 2012, were selected through the comprehensive computer literature search (Figure 1) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. The characteristics of the selected meta-analyses on the diagnostic performance are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four meta-analyses on the use of PET or PET/CT with different tracers in brain tumors, published from 2012, were selected through the comprehensive computer literature search (Figure 1) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. The characteristics of the selected meta-analyses on the diagnostic performance are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis demonstrated that the pooled sensitivity and specificity of 18 F-FDG PET or PET/CT in detecting brain metastases in patients with lung cancer were 21% and 100%, respectively. In particular, the sensitivity of this method is lower compared to that of contrast-enhanced MRI [24].…”
Section: Resultsmentioning
confidence: 99%
“…An early diagnosis of lung cancer may improve the administration of timely anticancer treatments, including surgery, chemoradiotherapy and immunotherapy, for patients with lung cancer, which can further improve the overall survival and progression-free survival (33)(34)(35). Clinically, PET/CT has been widely used for diagnosing human lung cancer and evaluating metastatic lesions (36). Previous studies have indicated that contrast agent is useful in PET/CT scanning of human lung cancer (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis demonstrated that the pooled sensitivity and specificity of 18 F-FDG PET or PET/CT in detecting brain metastases in patients with lung cancer were 21% and 100%, respectively. In particular, the sensitivity of this method is lower compared to that of contrast-enhanced MRI [19].…”
Section: Diagnosis Of Brain Metastasesmentioning
confidence: 95%